A systematic review of interventions to reduce anticholinergic burden in older people with dementia in primary care. (7th May 2022) - Shawaqfeh, Bara'a; Hughes, Carmel M.; McGuinness, Bernadette; Barry, Heather E.
Abstract: Objective: This systematic review aimed to assess the types and effectiveness of interventions that sought to reduce anticholinergic burden (ACB) in people with dementia (PwD) in primary care. Methods: One trial registry and eight electronic databases were systematically searched to identify eligible English language studies from inception until December 2021. To be eligible for inclusion, studies had to be randomised controlled trials (RCTs) or non‐randomised studies (NRS), including controlled before‐and‐after studies and interrupted time‐series studies, of interventions to reduce ACB in PwD aged ≥65 years (either community‐dwelling or care home residents). All outcomes were to be considered. Quality was to be assessed using the Cochrane Risk of Bias tool for RCTs and ROBINS‐I tool for NRS. If data could not be pooled for meta‐analysis, a narrative synthesis was to be conducted. Results: In total, 1880 records were found, with 1594 records remaining after removal of duplicates. Following title/abstract screening, 13 full‐text articles were assessed for eligibility. None of these studies met the inclusion criteria for this review. Reasons for exclusion were incorrect study design, ineligible study population, lack of focus on reducing ACB, and studies conducted outside the primary care setting. Conclusions: This 'empty' systematic review highlights the lack of interventions to reduce ACB in PwD within primary care, despite this being highlighted as a priority area for research in recent clinical guidance. Future research should focus on development and testing of interventions to reduce ACB in this patient population through high‐quality clinical trials. Key points: Anticholinergic burden (ACB) remains high among people with dementia (PwD) despite known risks to physical and cognitive functioning. Reducing ACB in PwD is essential to improve quality of life and reduce negative outcomes. The literature was systematically reviewed to assess the types and effectiveness of interventions to reduce ACB among PwD in primary care. However, no studies met the inclusion criteria for this review, highlighting the lack of high‐quality evidence in this area. There is a clear need for future studies to develop and test interventions to reduce ACB in PwD, particularly in the primary care setting, using robust study designs.